(untitled) (Research, Society and Development, 2024)
Depression, a prevalent psychiatric condition, affects over 300 million people worldwide, according to the World Health Organization. Despite the effectiveness of conventional treatments such as antidepressants and psychotherapy, many patients do not respond adequately, sparking interest in alternative therapies. The objective of this review is to explore the therapeutic potential of essential oils from lavender, bergamot, Sicilian lemon, clove, ylang-ylang, chamomile, and lemon balm in the treatment of anxiety and depression, based on extensive bibliographic research from databases like SciELO, PubMed, SciFinder, and Elsevier. The results show that lavender essential oil significantly reduces depression symptoms through inhalation and topical application. Bergamot, clove, and Sicilian lemon oils also demonstrated antidepressant properties. However, ylang-ylang oil did not show significant results in reducing depressive behaviors. It is important to note that further research is needed to understand their mechanisms of action and strengthen the evidence base. While alternative therapies offer benefits, they should not replace established pharmacological treatments.